Female Security System Using IoT and Mobile Computing - FeSecure - Lakshmi, R; Yashaswini, K.M; Vinutha, S; Likitha, G; Nithin, J (International Journal of Computer Sciences and Engineering, 2021)
location tracker, With the proliferation of crimes in today’s world, safety of the women is one of the most serious and compulsive requirements. Number of crimes against women is increasing drastically and over 4 million rape cases were reported across India between 2001 and 2017. Not only just this number, innumerable number of women is becoming victims of harassments and violence. Considering this alarming situation in the country, a wearable women safety device is proposed in this paper. The proposed model of the device “FeSecure” consists of hardware and software modules. The hardware module is designed considering the scenario wherein the attackers seize the mobile phone from victim and victim is incapable of accessing her phone. The model of wearable device consists of GPS, GSM and sensors. Sensors read vital parameters from the victim such as body temperature and heart rate, and alerts will be sent to emergency contacts and nearby police station with the help of location tracker module if any irregularities are detected in the read parameters. To alleviate the false positive alerts, reverse alarm, and alarm fatigue is incorporated in the system. Along with this, android application is also built that has various features like panic button, fingerprint recognition and voice recognition which can be used by victim to send alerts.